1981
DOI: 10.1017/s0021859600036832
|View full text |Cite
|
Sign up to set email alerts
|

Sire-breed comparison of carcass composition of steers from Angus dams

Abstract: SUMMARYBody composition of 324 steers from Angus dams by ten different sire breeds was compared at constant age. Progeny of the large European breeds and the Friesian attained heavier fasted live weights and carcass weights than the local Angus and Hereford breeds. Friesian cross-breds had the lowest dressing percentage. The Blonde d'Aquitaine and Limousin crosses had the lightest bone weights and this was reflected in high meat yields. The European breeds had the leanest carcasses, the traditional beef breeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0
2

Year Published

1986
1986
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
4
9
0
2
Order By: Relevance
“…In a New Zealand study, Muir et al (2000) found that despite differences in size, conformation and fatness between Hereford, Friesian and Hereford cross Friesian steers, overall yield of saleable high value cuts (cube roll, striploin and tenderloin expressed as a percentage of total carcass weight) was similar between breeds when slaughtered at the same weight or level of maturity. Similar results were reported by Barton (1971Barton ( , 1972, Truscott et al (1976), Everitt et al (1980), Bass et al (1981), Nour et al (1981Nour et al ( , 1983b, Bertrand et al 1983, Patterson et al (1985, Stiffler et al (1985) and Butler-Hogg et al (1988). Branaman et al (1962) found no significant difference in the total percentage of rib, round and loin cuts in Holstein and Hereford steer carcasses.…”
Section: Yield Of High Value Cutssupporting
confidence: 86%
See 2 more Smart Citations
“…In a New Zealand study, Muir et al (2000) found that despite differences in size, conformation and fatness between Hereford, Friesian and Hereford cross Friesian steers, overall yield of saleable high value cuts (cube roll, striploin and tenderloin expressed as a percentage of total carcass weight) was similar between breeds when slaughtered at the same weight or level of maturity. Similar results were reported by Barton (1971Barton ( , 1972, Truscott et al (1976), Everitt et al (1980), Bass et al (1981), Nour et al (1981Nour et al ( , 1983b, Bertrand et al 1983, Patterson et al (1985, Stiffler et al (1985) and Butler-Hogg et al (1988). Branaman et al (1962) found no significant difference in the total percentage of rib, round and loin cuts in Holstein and Hereford steer carcasses.…”
Section: Yield Of High Value Cutssupporting
confidence: 86%
“…Branaman et al (1962) slaughtered Holstein and Hereford steers at approximately the same age and found no significant difference in the percentage of separable lean. Bass et al (1981) found no differences in lean meat between dairy and British beef crosses when finished on pasture, but both were different to the heavy, late maturing European breeds (e.g. Charolais and Simmental).…”
Section: Saleable Meat Yieldmentioning
confidence: 63%
See 1 more Smart Citation
“…It is only quite recently that characteristics of carcasses of these breeds and crosses of these and other breeds have been reported by New Zealand workers (Campbell 1970;Hight et al 1973;Carter 1975;Bass et al 1981;Baker & Carter 1982). In contrast both breed and heterosis effects on carcass traits of steers and been reported in many North American studies (e.g., Cundiff 1970;Long 1980;Gregory et al 1982).…”
Section: Introductionmentioning
confidence: 98%
“…Cette inversion des effets d'hétérosis entre les deux périodes (9-15 et 15-18 mois) est plus élevée pour les croisés Charolais x Limousins qui présentaient avant 15 mois l'hétérosis spécifique le plus élevé. R ENAND , 1985) ou sur un troupeau de vaches allaitantes (B ASS et al, 1981 ;G REGORY et al, 1982 ;R AHNEFELD et C ll., 1983) les résultats concernant le poids en fin d'engraissement par jour d'âge se situent entre — 5 et -10 % pour l'écart entre les races Limousine et Charolaise avec une moyenne de — 7 %. Notre résultat est donc cohérent avec ce dernier chiffre, bien que plus faible si on admet qu'en croisement on n'obtient que la demi-différence des races pures.…”
Section: Les Effets D'hétérosisunclassified